Service Quality, Trust, and Satisfaction: A Mediation Analysis in the Context of New Electricity Installations - Syahrun, Muhammad; Khan, Zafar (Journal of Organizational and Human Resource Development Strategies, 2025)
This study investigates the direct and indirect effects of service quality on customer trust and customer satisfaction in the context of new electricity installations at PT. PLN (a government company), Maumere Branch, Sikka Regency. Using a quantitative approach, data were collected through 127 distributed questionnaires to prospective customers registering for new electricity installations. A non-probability sampling technique was employed, specifically the accidental sampling method, wherein respondents were selected based on their availability at the PLN registration counter. The results of structural equation modeling analysis indicate that service quality exerts a positive and significant influence on both customer trust and customer satisfaction. Furthermore, trust significantly enhances customer satisfaction. The mediation analysis confirms that customer trust partially mediates the relationship between service quality and satisfaction. These findings highlight the critical role of trust as a mediating variable and underscore the importance of service quality improvements in fostering customer satisfaction in public utility services.